'Who's actually gonna read this?' An evaluation of staff experiences of the value of information contained in written care plans in supporting care in three different dementia care settings. Issue 6 (4th July 2017) - Drummond, C.; Simpson, A.
Accessible summary: What is known on the subject?: A written plan is designed to improve communication and co‐ordinate care between mental health inpatient wards and community settings. Reports of care plan quality issues and staff and service user dissatisfaction with healthcare bureaucracy have focused on working age mental health or general hospital settings. Little is known about mental health staff perspectives on the value of written care plans in supporting dementia care. What this paper adds to existing knowledge?: Competing demands on staff time and resources to meet administrative standards for care plans caused a tension with their own professional priorities for supporting care. Mental health staff face difficulties using electronic records alongside other systems of information sharing. Further exploration is needed of the gap between frontline staff values and those of the local organization and managers when supporting good dementia care. What are the implications for practice?: Frontline staff should be involved in designing new information systems including care plans. Care plan documentation needs to be refocused to ensure it is effective in enabling staff to communicate amongst themselves and with others to support people with dementia. Practice‐based mentors could be deployed to strengthen good practice in effective information sharing. Abstract: Background: Reports of increased healthcare bureaucracy and concerns over care plan quality have emerged from research and surveys into staff and service user experiences. Little is known of mental health staff perspectives on the value of written care plans in supporting dementia care. Aim: To investigate the experiences and views of staff in relation to care planning in dementia services in one National Health Service (NHS) provider Trust in England. Method: Grounded Theory methodology was used. A purposive sample of 11 multidisciplinary staff were interviewed across three sites in one NHS Trust. Interviews were transcribed, coded and analysed using the constant comparative method. Findings: Five themes were identified and are explored in detail below: (1) Repetition; (2) the impact of electronic records on practice; (3) ambivalence about the value of paperwork; (4) time conflicts; and (5) alternative sources of information to plan care. Discussion: Participants perceived that written care plans did not help staff with good practice in planning care or to support dementia care generally. Staff were frustrated by repetitive documentation, inflexible electronic records and conflicting demands on their time. Implications for practice: Frontline staff should be involved in designing new information systems including care plans.